Perinatal Palliative Care: Cultural, Spiritual, and Religious Considerations for Parents—What Clinicians Need to Know - Kain, Victoria J. (Frontiers in Pediatrics, 2021)
For perinatal palliative care (PPC) to be truly holistic, it is imperative that clinicians are conversant in the cultural, spiritual and religious needs of parents. That cultural, spiritual and religious needs for parents should be sensitively attended to are widely touted in the PPC literature and extant protocols, however there is little guidance available to the clinician as to how to meet these needs. The objective of this review article is to report what is known about the cultural, spiritual and religious practices of parents and how this might impact neonates who are born with a LLFD. The following religions will be considered – Islam, Buddhism, Hinduism, Judaism and Christianity – in terms of what clinicians need to know about rituals and doctrine related to perinatal palliative care. Cultural and spiritual needs will also be addressed. The following religions will be considered – Islam, Buddhism, Hinduism, Judaism and Christianity – in terms of what may be helpful for clinicians to consider regarding rituals and doctrine related to PPC. Data Sources include PubMed, Ovid, PsycInfo, CINAHL, and Medline from Jan 2000 – June 2020 using the terms ‘perinatal palliative care’, ‘perinatal hospice’, ‘cultur*’ and ‘religiou*’. Inclusion criteria includes all empirical and research studies published in English that focus on the cultural and religious needs of parents who opted to continue a pregnancy in which the fetus had a life-limiting condition or had received perinatal palliative care. Grey literature from religious leaders and about the Great Religions were also considered. Results from these sources contributing to the knowledge base of cultural, spiritual and religious dimensions of perinatal palliative care are considered in this paper.